Early rumen development in calves: Biological processes and nutritional strategies—A mini-review - M.H. Ghaffari; H.M. Hammon; C. Koch (JDS Communications)
The transformation of the reticulo-rumen (hereafter rumen) from a monogastric state to a functional rumen during early calf development is driven by complex transcriptional reprogramming and changes in metabolic pathways. This transformation involves coordinated morphogenesis, gene regulation, and microbial colonization. These processes promote muscle growth, epithelial differentiation, and efficient nutrient absorption and fermentation. Microbial succession begins at birth and is characterized by interaction with the host and the early introduction of solid feed. This succession establishes anaerobic, fibrolytic, and amylolytic bacterial species that are critical for nutrient absorption and productivity. In addition, optimizing grain processing in calf diets along with ensuring adequate forage intake is critical to promoting effective papilla development while maintaining stable fermentation and supporting a stable ruminal pH. Together, these factors are essential for implementing targeted nutrition and management strategies to improve calf health and productivity.